How healthy is your mate? Sex-specific consequences of parasite infections in the moth Helicoverpa armigera. (August 2021) - Gao, Ke; van Wijk, Michiel; Dang, Quynh T.D.; Heckel, David G.; Zalucki, Myron P.; Groot, Astrid T.
Abstract : Parasites can play an important role in host sexual selection. According to the 'Hamilton & Zuk hypothesis', females acquire benefits from choosing parasite-free or parasite-resistant males based on their secondary sexual traits (e.g. colourful plumage) as indicators of heritable parasite resistance. However, females may also gain benefits by avoiding sexually transmitted parasites or acquiring more parental care, higher quality sperm and nuptial gifts provided by uninfected males. Here we tested how the presence of the Ophryocystis elektroscirrha -like parasite (OE-like) affected longevity, reproduction and mating frequency in the moth Helicoverpa armigera . We found that OE-like infection affected the sexes differently: the life span of uninfected males was reduced when paired with infected females, while these females had higher reproductive output than when paired with infected males. These results suggest some form of terminal investment by infected males. When we assessed the effect of OE-like infections on female calling behaviour and sex pheromone signal, we found that the OE-like parasite did not affect the female's pheromone signal in quality or quantity, but it did reduce her reproductive output, suggesting that infected females reallocate resources to maintain an attractive sex pheromone signal. In mate choice experiments, when females were the choosing sex, infected females mated significantly more often with uninfected than with infected males. Since these females produced approximately 12% more offspring, and uninfected females did not prefer uninfected or infected males, these results indicate female choice for uninfected males. Unexpectedly, when we compared the calling behaviour of the two females that were caged together, we found that infected females called significantly earlier than uninfected females, while this was not the case when females were housed alone. Thus, OE-like infection affects reproductive strategies in both males and females, but in different ways, which suggests sex-specific parasite-mediated selection. Highlights: A neogregarine parasite affects H. armigera male longevity and female reproduction. Infected females produce more offspring with uninfected than infected males. Male choice is affected by when female calls not by her infection status. Infected females call significantly earlier than uninfected females. Sex-specific effects of parasite infection result in sex-specific mating strategies.